Analisis Sistem Pendingin Mesin Bantu Generator Menggunakan Media Air Laut - Sya'bani, Ahmad; Lesmana, I Gede Eka (VISA: Journal of Vision and Ideas, 2024)
The generator converts mechanical power into electrical power because the wire coil inside cuts the magnetic force, causing a voltage and generating an electric current through a cable connected to a sliding ring as the connecting terminal for the current to discharge. Because the high temperatur of the cooling system is caused by dirty tubes in the Fresh Water Cooler and leaking seawater pipes leading to the seawater pump. For this reason, the generator cooling system must always be maintained routinely so that it does not experience problems, especially when the generator engine is started with a temperatur of not more than 85° C. Generator cooling system maintenance. The subject that is the focus of this research is the selection of data sources for analysis of the causes of high coolant temperaturs in diesel generator motors aboard the MT.TY. The results of the research The temperatur calculations were carried out from 14 to 20 June 2023 that the efficiency of the generator was positive at 7.69% which was good from 14 June 2023 08-12 until 17 June 2023 16-20. This shows that the generator is working well and needs to be stabilized, as well as a positive water cooling efficiency of 13.54%. This shows that with a water debit of 3 L/m it functions properly and does not need maintenance, and the decrease in seawater cooling pressure entering the Water Fresh Water Cooler can be caused by a dirty filter or a drop in pump pressure, which can increase the engine cooling water temperatur. master on board.